2006
DOI: 10.1097/01.mph.0000212939.89984.d2
|View full text |Cite
|
Sign up to set email alerts
|

Severe Anemia Owing to Occult Pulmonary Hemorrhage

Abstract: The purpose of this paper is to increase the awareness about pulmonary hemorrhage as a possible cause of microcytic hypochromic anemia and to delineate diagnostic difficulties and possible pitfalls. An instructive case of anemia of unclear origin referred to our institution for a hematologic workup is presented. Microcytic hypochromic anemia owing to repeated occult alveolar hemorrhages was the only clinical sign of idiopathic pulmonary hemosiderosis in this case. The laboratory finding constellation in such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…Plasma ferritin level can elevated because of the alveolar synthesis and release into the circulation and do not reflect the iron deposits of the body. 15 In the our study, all of them had the decreased transferrin saturation and MCV. In contrary of literature, three of our patients had the hypoferritinemia.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Plasma ferritin level can elevated because of the alveolar synthesis and release into the circulation and do not reflect the iron deposits of the body. 15 In the our study, all of them had the decreased transferrin saturation and MCV. In contrary of literature, three of our patients had the hypoferritinemia.…”
Section: Discussionsupporting
confidence: 46%
“…13 It is probably due to not only to the lack of hemoptysis, but to the fact that iron deficiency anemia may be the first and the only manifestation of IPH. 14,15 In our patients, the atypical clinical manifestations included presenting with severe anemia are repeated blood transfusions and absence of hemoptysis in four of patients. Our patients had iron deficiency anemia as a only manifestations of IPH.…”
Section: Discussionmentioning
confidence: 65%
“…A lack of prominent respiratory symptoms does not preclude a diagnosis of DAH. Minkov et al [21] reported a 6-year-old with severe microcytic, hypochromic anemia. After the hematologic evaluation in that patient was nonrevealing, a more careful history uncovered mild cough and exercise intolerance, and chest films and computed tomography confirmed the diagnosis of IPH.…”
Section: Clinical Presentationmentioning
confidence: 98%
“…1 We have also identified a case of silent IPH, where the presence of atypical features of otherwise characteristic iron-deficiency anemia (IDA)-normal serum ferritin in the absence of systemic inflammation-led to intensive investigation. The eventual diagnosis of IPH was made by carefully targeted assessment of pulmonary irregularities.…”
Section: To the Editormentioning
confidence: 99%